17) 11.1
18) 21.4
19) 30.5
20) 16.5
21) 26.5
<span>B(n) = A(1 + i)^n - (P/i)[(1 + i)^n - 1]
where B is the balance after n payments are made, i is the monthly interest rate, P is the monthly payment and A is the initial amount of loan.
We require B(n) = 0...i.e. balance of 0 after n months.
so, 0 = A(1 + i)^n - (P/i)[(1 + i)^n - 1]
Then, with some algebraic juggling we get:
n = -[log(1 - (Ai/P)]/log(1 + i)
Now, payment is at the beginning of the month, so A = $754.43 - $150 => $604.43
Also, i = (13.6/100)/12 => 0.136/12 per month
i.e. n = -[log(1 - (604.43)(0.136/12)/150)]/log(1 + 0.136/12)
so, n = 4.15 months...i.e. 4 payments + remainder
b) Now we have A = $754.43 - $300 = $454.43 so,
n = -[log(1 - (454.43)(0.136/12)/300)]/log(1 + 0.136/12)
so, n = 1.54 months...i.e. 1 payment + remainder
</span>
Answer:
$64,000
Step-by-step explanation:
Friday, 45 / 9 = 5
So the investment will double 5 times
First time
2,000 (starting investment) × 2 = 4000
Second time
4000 × 2 = 8000
Third time
8000 × 2 = 16000
Fourth time
16000 × 2 = 32000
Fifth and final time
32000 × 2 = 64000
$64,000
The factor theorem says that for a function f(x), if f(a) = 0, then (x - a) is a factor of f(x).
For f(x) = 2x^4 + 22x^3 + 60x^2
f(-5) = 2(-5)^4 + 22(-5)^3 + 60(-5)^2 = 2(625) + 22(-125) + 60(25) = 1250 - 2750 + 1500 = 0
Therefore, x - (-5) = x + 5 is a factor of f(x).
Answer:
3802 8/9
Step-by-step explanation:
So what you do is you make 52 1/3 and 72 2/3 improper fractions like 157/3 and 218/3. Then you multiply and get 34218/9. Then you simplafiy and get 3802 8/9